Assessing the impact of headaches and the outcomes of treatment: A systematic review of patient-reported outcome measures (PROMs). (June 2018) - Haywood, Kirstie L; Mars, Tom S; Potter, Rachel; Patel, Shilpa; Matharu, Manjit; Underwood, Martin
Aims: To critically appraise, compare and synthesise the quality and acceptability of multi-item patient reported outcome measures for adults with chronic or episodic headache. Methods: Systematic literature searches of major databases (1980–2016) to identify published evidence of PROM measurement and practical properties. Data on study quality (COSMIN), measurement and practical properties per measure were extracted and assessed against accepted standards to inform an evidence synthesis. Results: From 10, 903 reviewed abstracts, 103 articles were assessed in full; 46 provided evidence for 23 PROMs: Eleven specific to the health-related impact of migraine (n = 5) or headache (n = 6); six assessed migraine-specific treatment response/satisfaction; six were generic measures. Evidence for measurement validity and score interpretation was strongest for two measures of impact, Migraine-Specific Quality of Life Questionnaire (MSQ v2.1) and Headache Impact Test 6-item (HIT-6), and one of treatment response, the Patient Perception of Migraine Questionnaire (PPMQ-R). Evidence of reliability was limited, but acceptable for the HIT-6. Responsiveness was rarely evaluated. Evidence for the remaining measures was limited. Patient involvement was limited and poorly reported. Conclusion: While evidence is limited, three measures have acceptable evidence of reliability and validity: HIT-6, MSQ v2.1 and PPMQ-R. Only the HIT-6 has acceptable evidence supporting its completion by all "headache" populations.